Canadian Forum on Combined Organ Transplantation. Issue 6 (June 2016) - Cantarovich, Marcelo; Blydt-Hansen, Tom D.; Gill, John; Tinckam, Kathryn; Schiff, Jeffrey; Alwayn, Ian; Bain, Vince; Dipchand, Anne I.; Isaac, Debra; Kim, S. Joseph; Lien, Dale; Zaltzman, Jeffrey; et al.
Abstract : Abstract: The Canadian Society of Transplantation and Canadian Blood Services conducted a consensus forum on combined renal/nonrenal transplants, as they are not part of Canadian organ-specific allocation models at present. The purpose of this initiative was to make recommendations, develop eligibility criteria, and a decision-making model on listing and allocation. Forty-two participants with expertise in combined transplantation participated in the consensus forum. The United States and Canadian data were reviewed. The consensus forum made recommendations regarding the following: (1) investigation of etiology, severity, duration, and level of renal dysfunction; (2) documentation of degree of nonreversible kidney injury; (3) eligibility for combined (either simultaneous or staged) transplantation; (4) research. Key recommendations were: (1) patients with end-stage nonrenal disease with estimated glomerular filtration rate less than 30 mL/min per 1.73 m 2 for longer than 1 month or on dialysis less than 3 months, who fulfill criteria for nonreversibility of renal dysfunction (by level and duration of renal dysfunction, imaging, and pathology findings), would be eligible for combined renal/nonrenal transplantation; (2) patients on dialysis longer than 3 months would be eligible for combined renal/nonrenal transplantation; (3) staged renal after nonrenal transplantation with subsequent prioritized allocation of renal transplant was endorsed in selected cases. The validation and impact of these recommendations on allocation will require further studies. Abstract : The authors report on the conclusions of a Canadian Consensus Forum devoted to renal/nonrenal transplantations with regard to eligibility, listing, and allocation. They produce useful recommendations about investigations of renal dysfunction, criteria of nonreversibiity of renal dysfunction, eligilibity for combined transplantation, and research.